Demographic Profile of Diabetic Foot Ulcers - Mohammad Omar Shah; HuzaifaNazir Tak; MS Moosabba (International Journal of Health and Clinical Research, 2021)
Background and objective: Diabetes associated problems are the second most common cause of lower limb amputations in India. We conducted this study to find out the socio-demographic profile and factors associated with diabetic foot ulcers.Materials and methods: This prospective non-randomized control study was conducted at Yenepoya Medical College Hospital on patients with diagnosed diabetic foot who were chosen by purposive sampling from October 2012 to September 2014. A total of 75 patients were chosen for the study after taking an informed verbal consent. Data was collected using questionnaire regarding sociodemographic profile, complications and associated factors. Results: Majority of the patients receiving treatment for diabetic foot were males. The average duration of diabetes mellitus observed was for 5-10 years. Our study also revealed that neuropathy was the most common complication associated with diabetic foot. Conclusion: Regular monitoring of blood sugar levels and foot screening should be done for diabetic as well as non-diabetic older adults for early detection of risk factors to reduce the foot complications.